PERAN PUBLIC INFORMATION OFFICERS DALAM KOMUNIKASI LAYANAN PERPUSTAKAAN DIGITAL MELALUI FACEBOOK - Purwadi, Purwadi; Irwansyah, Irwansyah (BACA: Jurnal Dokumentasi dan Informasi, 2019)
This study aims to find out communication models on analog versus digital library services through Facebook; and the important role of PIO in digital library services. This study uses a qualitative descriptive method with literature studies. This study shows that there has been a shift in the model and role of library service communication from analog to digital. This can be seen from the role of PIO as: (1) digital library information content creators; (2) digital library promotional content creators; (3) communication managers and disseminator on information and promotions on social media (in the context of this article is Facebook); and (4) communication links between leaders and audiences. The recommendation of this study is that library managers must recognize the importance of a new communication model in library management through Facebook.